When Phones Take Over: How Self-Management Bridges the Gap to Communication - Nur Wahyunianti Dahri; Heru Kurnianto Tjahjono; Mohsin Shaikh; Muhammad Aqil; Mashitah Syam (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
In the contemporary digital era, the pervasive use of smartphones, particularly among Generation Z, has become a prevalent phenomenon across various settings, including professional environments. One of the deleterious effects of this phenomenon is what has been termed "phone snubbing behavior" (PSB), which is defined as the tendency to ignore in-person social interactions due to excessive focus on mobile devices. The objective of this research is to validate the mediating function of self-management or self-control on the relationship PSB, which is defined as the excessive use of smartphones during social interactions that ultimately impedes communication among Generation Z employees in the West Sulawesi government among the selected population. It is therefore recommended that they enhance their self-control to mitigate the impact of PSB and promote effective communication in the work environment. The study employed a purposive sampling technique, selecting a sample of 228 respondents from a total population of 7.112. The data analysis was conducted using SEM (Structural Equation Modeling). The study's findings indicate that PSB exerts a negative influence on social interaction; PSB has a negative impact on self-control; Self-control has a positive effect on social interaction; Self-control directly mediates the influence of PSB on social interaction. This research makes a significant contribution by delving deeper into the behavioral influences of PSBs in a governmental context and suggesting a practical approach through enhancing self-control to reduce technology-induced disruptions to interpersonal communication. This issue is increasingly relevant in today's digital age.